Home‐Based Work and Women’s Labor Force Decisions - Edwards, Linda N.; Field‐Hendrey, Elizabeth (Journal of Labor Economics, 2002)
Home‐based work differs from other employment because the work site is the home itself. This difference means that the fixed costs of working at home are less than the fixed costs of working on site and that home‐based workers may engage in joint market and household production. Using data from the 1990 Census, we find that home‐based work is an attractive option for women for whom the fixed costs of work are high—women who have small children, are disabled, or live in rural areas—and that home‐based workers are more likely to choose self‐employment than are on‐site workers.